The implied author concept and controversy - Kindt, Tom 1970-; Müller, Hans-Harald 1943- (de Gruyter, 2006)
This book addresses itself to the concept of the implied author, which has been the cause of controversy in cultural studies for some fifty years. The opening chapters examine the introduction of the concept in Wayne C. Booth's "Rhetoric of Fiction" and the discussion of the concept in narratology and in the theory and practice of interpretation. The final chapter develops proposals for clarifying or replacing the concept.
Keywords: Implied author (Rhetoric); Erzählforschung